Growth under pressure: The pros and cons of polyploidy induced by stress - Lilijana Sarabia Oliver; Paulo B. Belato; Joshua Silva; Anna Selmecki; Donald T. Fox; Adrienne H. K. Roeder (Proceedings of the National Academy of Sciences, 2026)
In native environments, organisms are faced with an array of acute or chronic stresses. These stresses include toxins, pathogens, and physical injury. An increasingly recognized response to diverse stresses is whole genome doubling or polyploidy. This transformative cellular property alters genome integrity, cellular structure, and tissue architecture. Whether polyploidy is a positive, negative, or neutral outcome of a stress is a current topic of investigation in numerous contexts including during fungal infection of plants and animals, during regeneration of wounded tissues, and in human diseases such as cancer. In this review, we highlight the wide range of stresses that promote polyploidy in fungal, plant, and animal contexts. Specifically, we highlight major mechanisms that lead to stress-induced polyploidy within somatic or germline tissues through alteration of the cell cycle. We discuss the impact of such stress-induced polyploidy on genomes, cells, and tissues and emphasize commonalities across organisms and biological scales. A common theme that has emerged is that polyploidy facilitates numerous subsequent genomic and cellular changes following abrupt stresses, and these changes can impact tissue architecture and function.